2008
DOI: 10.1681/asn.2008030336
|View full text |Cite
|
Sign up to set email alerts
|

Rap1b GTPase Ameliorates Glucose-Induced Mitochondrial Dysfunction

Abstract: The role of tubular injury in diabetic nephropathy is relatively unknown, despite that apoptosis of tubular epithelial cells is commonly observed in human renal biopsies. The GTPase Ras-proximate-1 (Rap1b) is upregulated in the hyperglycemic state and is known to increase B-Raf, an antiapoptotic effector protein.In this study, the effects of high glucose on renal tubular apoptosis and the potential ability for Rap1b to ameliorate these effects were investigated. In the kidneys of diabetic mice, apoptotic tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 38 publications
5
83
0
Order By: Relevance
“…Assessment of Cellular Distribution of Cytochrome c-Confocal microscopy was employed to delineate the distribution of cytochrome c, as described previously (41). Cells were incubated with 25 nM Mitotracker dye (Mitotracker Red, Molecular Probes, Inc.) at 37°C for 10 min.…”
Section: Determination Of the Source Of Intracellular Ros Generation mentioning
confidence: 99%
“…Assessment of Cellular Distribution of Cytochrome c-Confocal microscopy was employed to delineate the distribution of cytochrome c, as described previously (41). Cells were incubated with 25 nM Mitotracker dye (Mitotracker Red, Molecular Probes, Inc.) at 37°C for 10 min.…”
Section: Determination Of the Source Of Intracellular Ros Generation mentioning
confidence: 99%
“…The features of tubulointerstitial histopathology include inflammation and apoptosis, which are not necessarily secondary to glomerular lesions. 7,[24][25][26] In addition, tubular injury alone is believed to be closely correlate with clinical manifestations of DKD, including the extent albumin excretion and its degradation in tubules. The latter may serve as a primary key site for the development of DKD, because tubular injury has been described to be a better predictor in the progression of the renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Although the pathogenesis of DKD still remains unclear, recent studies in animals and humans have led to an emerging concept that mitochondrial dysfunctions, which are pivotal events, lead to activation of various cellular processes and aberrant signaling in different cell types of the kidney. [7][8][9] Mitochondria are dynamic organelles that constantly undergo fusion and fission cycles to maintain a balance of cellular reticular network and mitochondrial turnover. 10 Their dynamics are regulated by profission proteins (Drp1 and Fis1) and profusion mediators (Mfn1/2 and OPA1).…”
mentioning
confidence: 99%
“…29 In addition, diabetic mouse models and in vitro studies have demonstrated that hyperglycemia induced mitochondrial fragmentation in podocytes, endothelial cells, and renal tubular cells. 7,30 Finally, WBCs are involved in the kidney's response to injury as evidenced by leukocyte infiltration in kidney tissues of patients with CKD and in experimental models. [31][32][33] Lower mtDNA copy number might alter the role of WBCs and platelets in injury response.…”
Section: Main Findingsmentioning
confidence: 99%
“…[3][4][5] Molecules that target mitochondrial function, including thiazolidinediones, have been proposed as therapeutic agents for protecting kidney function. [6][7][8][9] However, studies on measures of mitochondrial dysfunction and CKD at the population level have been limited.…”
mentioning
confidence: 99%